A metodologia ativa Peer Instruction e o uso do aplicativo Socrative: possibilidades de aprendizagem no curso técnico de Marketing - SILVA, Davi Fernando da (2019)
This dissertation is part of the Master’s Education Program of Universidade do Oeste Paulista – UNOESTE, in the field of research on Background Development and Pedagogical Practice of Teaching Staff. It was carried out to analyze the use of the Peer instruction approach jointly with the Socrative application in the learning of students attending the Marketing technical course. The theoretical basis to discuss the educational context and trends of senior high school is supported by authors such as Libâneo, Saviani, Frigotto and Ciavatta, Costa and Coutinho. To support education mediated by technologies one used studies carried out by Assis and Silva, Unesco, Coscarelli and Ribeiro, Rocha. The reference of the active Peer Instruction approach was based on Mazur, Diniz and Rocha. The research approach was a qualitative one, by means of field research, which comprised thirty (30) students and a teacher of Marketing Strategies, in the course of Marketing of a technical school of Presidente Prudente - SP. The data were collected by reports of applied questionnaires using the Socrative software; observation of peer interaction and questionnaires responded by students and their teacher. One used the MAXQDA software to help the organization and analysis of the collected data Classes were formed from the analysis which emerged from data triangulation, namely: Class 1. Potential of the Socrative application; Class 2. Peer Instruction and its implications for learning, being the results of such a class analyzed on the basis of the ARCS model, subdivided into attention, relevance, confidence and satisfaction and Class 3. The teacher’s action and vision in the use of the Peer Instruction approach jointly with the Socrative application. One came to the conclusion that the Socrative software is indeed an effective resource to help in the application of concept tests. Concerning the analysis according to John Keller’s motivational approach (ARCS), one noticed that the student’s attention was attracted, the relevance both of the material and of the approach itself was presented, the confidence was preserved during the field research and, consequently, the satisfaction was plainly felt. In the teacher’s action and vision class in the use of the approach, one managed to conclude that, if the teacher is open to new ways of teaching and participates in his continued background development, teaching by using the Peer Instruction approach jointly with the Socrative application provides an active and cooperative learning